2009
DOI: 10.1113/jphysiol.2009.172080
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Na+/Ca2+ exchanger in migration and contraction of rat cultured tendon fibroblasts

Abstract: In response to injury and inflammation of tendons, tendon fibroblasts are activated, migrate to the wound, and eventually induce contraction of the extracellular matrices to repair the tissue. .7 were expressed in cultured tendon fibroblasts. NCX2 mRNA was undetected. NCX3 expression was negligibly low. Immunofluorescence microscopy indicated that NCX1 protein localized in the plasma membrane especially at the microspikes of tendon fibroblasts. In the wound-healing scratch assay, the cells migrated toward the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…26 NCX1 is expressed on cells of mesenchymal origin, including fibroblasts, smooth muscle cells, and myofibroblasts, that all play key roles in aneurysm formation in KD patients. 10,13,[27][28][29] Transforming growth factor-β signaling leads to calcium flux in fibroblasts through NCX1 and results in increased expression of endothelial-mesenchymal transition (EMT)-related genes, including connective tissue growth factor and smooth muscle actin. 13 We have previously reported that myofibroblast-like cells expressing connective tissue growth factor in the wall of CAA and NCX1 may influence this process.…”
Section: Potential Role Of Ncx1 In Kd Pathogenesismentioning
confidence: 99%
“…26 NCX1 is expressed on cells of mesenchymal origin, including fibroblasts, smooth muscle cells, and myofibroblasts, that all play key roles in aneurysm formation in KD patients. 10,13,[27][28][29] Transforming growth factor-β signaling leads to calcium flux in fibroblasts through NCX1 and results in increased expression of endothelial-mesenchymal transition (EMT)-related genes, including connective tissue growth factor and smooth muscle actin. 13 We have previously reported that myofibroblast-like cells expressing connective tissue growth factor in the wall of CAA and NCX1 may influence this process.…”
Section: Potential Role Of Ncx1 In Kd Pathogenesismentioning
confidence: 99%
“…Cultured myofibers were separated from fibroblasts by the following way. To minimize the number of fibroblasts, which would otherwise eventually overgrow myofibers during culture (Sakamoto et al, 2007(Sakamoto et al, , 2009, the preparation was allowed to settle for 10 min. The sediments were transferred to a 60-mm dish and cultured overnight.…”
Section: Methodsmentioning
confidence: 99%
“…NCX1 has been reported to promote the migration of a diverse group of non-epithelial cells such as endothelial cells, oligodendrocytes, myofibroblasts, microglia, and pancreatic cancer cells (53)(54)(55)(56)(57)(58)(59)(60). Inhibition or knockdown of NCX1 reduced intracellular calcium and prevented migration.…”
Section: Discussionmentioning
confidence: 99%